HOLOCENE PALEOENVIRONMENTAL RECONSTRUCTION OF THE SUNDA SHELF , OFF NORTHEASTERN PENINSULAR MALAYSIA - Harrison, Emily I.; NC DOCKS at East Carolina University (2017)
In order to understand Holocene paleoenvironmental evolution of the western Sunda Shelf (southern South China Sea) , two gravity cores TER15-GC10A and TER15-GC9A were collected (2015) 33 and 37 km offshore of Kuala Terengganu (KT) , Peninsular Malaysia at ca. 60 m water depth. The cores were sampled every 1 cm and analyzed for three paleoenvironmental proxies; 1) bulk sediment magnetic susceptibility (BMS); 2) elemental analysis by x-ray fluorescence (XRF) spectrometry , and 3) foraminiferal content. Radiocarbon age estimates indicate that cores have a maximum age of ca. 8 , 400 cal. yr BP. BMS values decrease up-core (1.95 x 10-4-1.04 x 10-4 SI). XRF data also indicate a decrease up-core for Al (12.82%-17.05%) , Fe (5.45%-3.65%) , and Ti (0.78%-0.61%) with an inverse relationship to the concentration of Ca (3.29%-7.77%). This is interpreted to reflect a decrease in amount of terrestrial material supplied to the shelf over the last ca. 8 , 400 years , a dilution of detrital material by the local productivity of marine carbonates , and/or a stabilization of sea level. Cluster analysis indicates four groups of benthic foraminifera within the two cores. Within all four clusters Textularia sp. A , Heterolepa dutemplei , Asterorotalia milletti , and Hanzawaia nipponica were the most abundant species. Within three of the four groups , Textularia sp. A was the most abundant. Benthic foraminiferal assemblages , along with the presence of planktonic foraminifera suggest an open inner-shelf marine environment. Within the two cores , three paleoenvironmental episodes were recognized. The first episode occurred from ca. 8 , 400 cal. yr BP to ca. 6 , 500 cal. yr BP and was characterized by relatively high terrigenous input. At the beginning of this episode , sea level was at about -5 m rising to a maximum height of around +5 m by the mid-Holocene highstand (6 , 500 BP). The second episode (6 , 500 cal. yr BP-4 , 000 cal. yr BP) was transitional , from the relatively high influence of terrigenous material to a third episode , ...